2021
DOI: 10.3389/fpubh.2021.678768
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining Innovation Amid the COVID-19 Pandemic: Insights From the WISH Innovation Programme

Abstract: The World Innovation Summit for Health (WISH) hosts two innovation competitions as part of its biennial healthcare conference. During the COVID-19 pandemic, WISH received more than 350 applications for both competitions, of which 31 were shortlisted to showcase at the WISH 2020 virtual summit. Of the 31 showcasing innovations, 11 (35.5%) had suggested an alternative use to their innovation as a contribution to the global fight against COVID-19. As such, this article explores the apparent and urgent need for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Driven by the outbreak of COVID‐19, a particular issue of interest is the evolution of scientific novelty during unexpected crises beyond a more conventional scientific environment. The importance of scientific novelty became more salient during COVID‐19 since the key to attacking COVID‐19 and recovering from the aftermath of the pandemic lies in finding innovative and effective solutions (Azoulay & Jones, 2020; El Akoum & El Achi, 2021; Peters, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven by the outbreak of COVID‐19, a particular issue of interest is the evolution of scientific novelty during unexpected crises beyond a more conventional scientific environment. The importance of scientific novelty became more salient during COVID‐19 since the key to attacking COVID‐19 and recovering from the aftermath of the pandemic lies in finding innovative and effective solutions (Azoulay & Jones, 2020; El Akoum & El Achi, 2021; Peters, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturers, such as General Motors and Dyson, used their manufacturing capacities to create ventilators that were in short supply 6 . Analyzing 350 applications for two competitions, a study found that COVID‐19 has revolutionized the way where innovative solutions are generated (El Akoum & El Achi, 2021). That is, repurposing technologies and ideas could be effective and cost‐efficient for generating solutions to complex problems.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been an increasing provision of designated quiet spaces in sporting and entertainment venues (e.g. 'sensory-friendly' spaces in City of Surrey (n.d.), Canada; football stadiums in the FIFA World Cup [El Akoum & Dyer, 2022]). Within theatre, 'relaxed performances' have been introduced, which reduce sensory input and provide a non-judgmental environment for autistic audience members (Fletcher-Watson & May, 2018).…”
mentioning
confidence: 99%